Are there any questions? How Socrates became the most annoying man alive - Morrell, Kevin (London : SAGE Publications: SAGE Business Cases Originals, 2021)
The case discusses the ancient figure of Socrates and describes his style of questioning others' assumptions. Readers are invited to consider whether allowing a role for questions in the style of Socrates is useful in organizations. On the one hand, questioning of initial basic assumptions may expose inconsistencies or incoherence. This exposure could help to develop answers to potentially difficult questions about the true values or purpose of an organization. It could also, potentially, prevent future problems such as corporate scandals. Scandals can occur if company employees-especially those in top management-do not have a reasonable grasp on what "doing business in an ethical manner" means, for instance. Or it could reveal that some of our definitions for complex terms are very shallow and incomplete. On the other hand, perhaps it is impossible to accomplish even the simplest task if every first principle is called into doubt. Students may like to think about the balance between rigorous questioning of assumptions and the need to get things done.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Socrates; Organizational behavior -- Case studies; Management -- Methodology